1983
DOI: 10.1177/001112878302900304
|View full text |Cite
|
Sign up to set email alerts
|

Gender Issues in Juvenile Justice

Abstract: The federal JJDP legislation has had a differential impact on the pattern of admission of females and males to detention facilities and training schools, and also on the rate of admission relative to the total available youth population. These findings suggest a differential societal response, and also variable incidence of delinquency among females and males. Data from a self-report survey of high school youth corroborate the latter assumption and also findings that have been noted by others. Attachment to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…For example, criminologists have isolated patriarchal notions of social control and discrimination as the key determinants of who ends up in the juvenile justice system [Chesney-Lind, 1973;Reitsma-Street, 1991;Sarri, 1983]. Within psychology, researchers have put forward the notion of a gender paradox, where females who develop antisocial behaviour are believed to surpass a higher threshold of risk than their male counterparts and, by inference, must have been exposed to higher levels of risk or suffer from a more deviant manifestation of the disorder [Eme, 1992;Loeber and Keenan, 1994].…”
Section: Subtypes Of Female Offenders: Questioning a ''One Size Fits mentioning
confidence: 99%
“…For example, criminologists have isolated patriarchal notions of social control and discrimination as the key determinants of who ends up in the juvenile justice system [Chesney-Lind, 1973;Reitsma-Street, 1991;Sarri, 1983]. Within psychology, researchers have put forward the notion of a gender paradox, where females who develop antisocial behaviour are believed to surpass a higher threshold of risk than their male counterparts and, by inference, must have been exposed to higher levels of risk or suffer from a more deviant manifestation of the disorder [Eme, 1992;Loeber and Keenan, 1994].…”
Section: Subtypes Of Female Offenders: Questioning a ''One Size Fits mentioning
confidence: 99%
“…White middle-class juveniles are far more likely to be processed informally than their Black lower-class counterparts (e.g., Miller, 1996;Sarri, 1983). Also, White and middle class juveniles are more likely to be filtered out of the system at earlier decision points than are poor and minority juveniles (Bishop & Frazier, 1988).…”
Section: Court Context and Juvenile Court Decisionsmentioning
confidence: 99%
“…Among those that have (see Miller, 1996;Sarri, 1983), findings reveal that White middle-class juvenile offenders are far more likely to be processed informally than their Black lower-class counterparts. Miller's (1996) work on delinquent girls, which relied on a content analysis of investigation reports of girls on probation, found that juvenile court officials use classbased standards (specifically, middle-class) to make disposition recommendations) Among adults, Visher (1983) and Chiricos and Bales (1991) point to the interaction of race, gender, and indicators of class (e.g., unemployment), finding that the influence of gender on police and court decisions differs depending upon the person's race and class.…”
Section: Criers Liars and Manipulators: Probation Officers' Views Omentioning
confidence: 99%